2019
DOI: 10.1038/s41598-019-53475-w
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Results of the Steroid and Non-steroidal Anti-inflammatory Drug Treatments in Subacute Thyroiditis in relation to Persistent Hypothyroidism and Recurrence

Abstract: Subacute thyroiditis (SAT) is an inflammatory thyroid disease. The main purpose of the treatment is to relieve pain and control the inflammatory process. The aim of the present study was to evaluate the therapeutic effects of steroid and non-steroidal anti-inflammatory drugs (NSAIDs) in SAT. Initial laboratory data, treatment response, and long-term results of 295 SAT patients treated with ibuprofen or methylprednisolone were evaluated. After the exclusion of 78 patients, evaluation was made of 126 patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 20 publications
10
61
3
4
Order By: Relevance
“…A study in the 1990s has reported that TSH receptor antibodies became positive in many patients with SAT, probably resulting in thyroid dysfunction ( 28 ). While other studies have reported female and thyroid antibody positivity as risk factors for hypothyroidism ( 12 , 17 , 29 ), no statistical results could confirm the aforementioned factors in this study. Instead, CRP and TSH were found to be risk factors for hypothyroidism, especially CRP levels of more than 97.80 mg/L and TSH levels of less than 0.10 mIU/L.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A study in the 1990s has reported that TSH receptor antibodies became positive in many patients with SAT, probably resulting in thyroid dysfunction ( 28 ). While other studies have reported female and thyroid antibody positivity as risk factors for hypothyroidism ( 12 , 17 , 29 ), no statistical results could confirm the aforementioned factors in this study. Instead, CRP and TSH were found to be risk factors for hypothyroidism, especially CRP levels of more than 97.80 mg/L and TSH levels of less than 0.10 mIU/L.…”
Section: Discussioncontrasting
confidence: 99%
“…The risk of recurrence in patients with SAT was HLA-dependent, and the co-presence of HLA-B*18:01 and –B*35 was a determining factor ( 16 ). Some studies have shown that patients who received corticosteroid therapy tended to receive T4 therapy, whereas some studies have shown the opposite ( 13 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fever and palpitations were present in approximately half of the patients in parallel with findings in the literature, while weight loss was present in a small number of patients [3]. ESR and CRP levels were above the upper limit of normal, similar to data reported in the literature [1, 3, 4, 13]. In addition, some authors have suggested that there may be a 1- to 6-week delay between the onset of symptoms and the appearance of laboratory findings [3, 14].…”
Section: Discussionsupporting
confidence: 82%
“…Latrofa showed that the Anti-Tg epitope pattern in SAT is different from that in Hashimoto's disease and that the anti-Tg release in SAT disease is transient, with no autoimmune significance (10). It has been hypothesized that patients with autoimmune thyroid disease who have anti-TPO positivity may also develop subacute thyroiditis (8,11) Recently published studies have established that the clinical importance of overlapping of SAT and autoimmune thyroid disease is that autoimmunity has been demonstrated to increase the rate of permanent hypothyroidism after SAT (12)(13)(14)(15)(16). Until recently, an increase in the level of TRAb, just like anti-TPO and anti-Tg, was not expected in patients with SAT.…”
Section: Discussionmentioning
confidence: 99%